First catheter ablations in the Ministry of Health system of Peru: report of the initial experience. - Montañez-Valverde, Raúl A. (2019)
BACKGROUND: In 2015, the Ministry of Health (MINSA) of Peru inaugurated the first national center for electrophysiology studies in a public tertiary referral hospital with the purpose to provide healthcare access to the most underserved population. This study aims to describe the rate of success and complications of catheter ablation in this center since its inception, as well as the demographic characteristics of these patients. METHODS: This study is descriptive and retrospective. We used the medical record of the patients who underwent catheter ablation (first-time and re-do procedure) in the center from July 2015 to February 2018. RESULTS: 55 catheter ablations were performed in 53 patients, who were 35 (±15) years old and 47% male. 63.6% had a full MINSA health coverage, while 16.4% and 20% had partial MINSA coverage and no health coverage, respectively. Atrio-ventricular reentrant tachycardia mediated by accessory pathways was the most common (76.4%) electrophysiology diagnosis. The overall immediate success rate was 96.4%. No complications were reported. CONCLUSIONS: The efficacy and safety of this procedure are comparable to international standards. The main limitations might be the insufficiency of resources and inadequate diffusion of our center activity.